4(2x-4)+8+x+13=3(2x+4)+8

Simple and best practice solution for 4(2x-4)+8+x+13=3(2x+4)+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x-4)+8+x+13=3(2x+4)+8 equation:


Simplifying
4(2x + -4) + 8 + x + 13 = 3(2x + 4) + 8

Reorder the terms:
4(-4 + 2x) + 8 + x + 13 = 3(2x + 4) + 8
(-4 * 4 + 2x * 4) + 8 + x + 13 = 3(2x + 4) + 8
(-16 + 8x) + 8 + x + 13 = 3(2x + 4) + 8

Reorder the terms:
-16 + 8 + 13 + 8x + x = 3(2x + 4) + 8

Combine like terms: -16 + 8 = -8
-8 + 13 + 8x + x = 3(2x + 4) + 8

Combine like terms: -8 + 13 = 5
5 + 8x + x = 3(2x + 4) + 8

Combine like terms: 8x + x = 9x
5 + 9x = 3(2x + 4) + 8

Reorder the terms:
5 + 9x = 3(4 + 2x) + 8
5 + 9x = (4 * 3 + 2x * 3) + 8
5 + 9x = (12 + 6x) + 8

Reorder the terms:
5 + 9x = 12 + 8 + 6x

Combine like terms: 12 + 8 = 20
5 + 9x = 20 + 6x

Solving
5 + 9x = 20 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
5 + 9x + -6x = 20 + 6x + -6x

Combine like terms: 9x + -6x = 3x
5 + 3x = 20 + 6x + -6x

Combine like terms: 6x + -6x = 0
5 + 3x = 20 + 0
5 + 3x = 20

Add '-5' to each side of the equation.
5 + -5 + 3x = 20 + -5

Combine like terms: 5 + -5 = 0
0 + 3x = 20 + -5
3x = 20 + -5

Combine like terms: 20 + -5 = 15
3x = 15

Divide each side by '3'.
x = 5

Simplifying
x = 5

See similar equations:

| 5x^2-5x+600=0 | | x+21x=40 | | 2275+150.99x=4237.87 | | 2(4x+7)-9=-19 | | v^2-144=0 | | .125x-5=3 | | (3yx+y^2)dx+(x^2+xy)dy=0 | | 5x-6=3x-35 | | 62x+37=x-39 | | 7x+4.6=x+8 | | -6000+20x= | | c^2+2c-63= | | 6x-1+4=4-2x | | 3(15x+75)=540 | | 0.40(94)0= | | v^2-14vf+40f^2=0 | | 3x+4.8=19 | | 3x+2(x-1)=6x-9 | | 2(x-2)=2(2-3x) | | 8z-12=9z-17 | | X+384x=2502 | | 11x+3+60=32x | | f(x)=2x^2-6x | | x^2-24x+58=0 | | 4u^2+6u+9=0 | | 65+31x=45-12x | | 3x+4.9=x+6 | | 9x^6+32x^4+60x+27=0 | | 6c-15=-3c+12 | | 11p-3p=16 | | 16x^3-12x^2+20x-15=0 | | 8y-9+y=9(y-3) |

Equations solver categories